Gender norms and their implications for banana production and recovery in west Africa - Nkengla-Asi, L.; Olaosebikan, O.D.; Che, V.S.; Ngatat, S.; Zandjanakou-Tachin, Martine; Hanna, R.; Kumar, P. Lava (Emerald Publishing Limited, 2019)
This study uses the social relations framework to explore gender norms and relations surrounding banana production and banana bunchy top disease (BBTD) containment in six pilot communities in Cameroon and Nigeria. The objective of the study is to understand how gender norms and relations shape and influence access to information and benefit-sharing of productive resources among men and women banana farmers and implications for banana production recovery in the BBTD-affected regions and disease management. Twelve, sex-disaggregated focus group discussions with 120 farmers (78 women and 42 men banana farmers) and 24 key informants were conducted. Data on banana production, access to and decision-making rights over productive resources and social and gender norms influencing adoption were collected. Data were analyzed using a systematic content analysis approach. Results show inequalities stemming from inherent gender and social norms related to access to and decision making over productive resources limiting especially women farmers’ ability to effectively engage in training programs that could lead to adoption of recommendations and technologies. Opportunities to effectively participate in training activities were influenced by gender norms related to household decision making, gender-based labor division and multiple household tasks. Interventions and strategies to contain the spread of BBTD should consider gender-based constraints and opportunities embedded in the communities for optimal results. Social and gender differentiations that impede women should be addressed for inclusive participation. Failure to address harmful norms and gender differentiation in the underlying social structures will benefit one group of people in the community over another.